2012
DOI: 10.5423/ppj.oa.02.2012.0026
|View full text |Cite
|
Sign up to set email alerts
|

Growth Promotion of Pepper Plants by Pantoea ananatis B1-9 and its Efficient Endophytic Colonization Capacity in Plant Tissues

Abstract: The bacteria B1-9 that was isolated from the rhizosphere of the green onion could promote growth of pepper, cucumber, tomato, and melon plants. In particular, pepper yield after B1-9 treatment on the seedling was increased about 3 times higher than that of control plants in a field experiment. Partial 16S rDNA sequences revealed that B1-9 belongs to the genus Pantoea ananatis. Pathogenecity tests showed non-pathogenic on kimchi cabbage, carrot, and onion. The functional characterization study demonstrated B1-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…In fact, only one other study on P. ananatis B1-9 strain isolated from the rhizosphere of onions showed potential for promoting plant growth in peppers, cucumbers, and melons (Kim et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, only one other study on P. ananatis B1-9 strain isolated from the rhizosphere of onions showed potential for promoting plant growth in peppers, cucumbers, and melons (Kim et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Auxins are typically used in agriculture to stimulate plant growth through root development (Benjamins and Scheres, 2008). According to Kim et al (2012), the production of IAA by P. ananatis B1-9 is the most important factor for growth and fruit production in pepper plants. Another study has shown that P. ananatis 125NP12 isolated from tomato plants is capable of producing IAA.…”
Section: Discussionmentioning
confidence: 99%
“…Siderophore production. The production of siderophores was described for several Pantoea species, such as Pantoea agglomerans, Pantoea eucalyptii (Viruel et al, 2011), Pantoea allii (Pereira and Castro, 2014), Pantoea ananatis (Kim et al, 2012;Loaces et al, 2011), as well as for other Pantoea species (Loaces et al, 2011). However, little is known about these siderophores.…”
Section: Promising Bacterial Genera For Agricultural Practicesmentioning
confidence: 99%
“…strains (Trifi et al, 2017). In addition, nutrient based promoting traits, such as phosphate solubilization or nitrogen fixation (Kim et al, 2012) were described. The biocontrol potential of Pantoea spp.…”
Section: Promising Bacterial Genera For Agricultural Practicesmentioning
confidence: 99%
See 1 more Smart Citation